WebWordPro version 2.0 the web-based word processing system / Lin Koon How - Lin , Koon How (2000)
Nowadays in this era of information technology computerized word processors have become a very common and essential need to everyone. From leisure to serious manner, it is used for typing letters, assignments, reports, paperwork and etc. It also enables people to keep data and manage it in a more secure and efficient way. With the current popularity and expansion of the Internet, Web-based applications become a new platform for the evolution of business system. Well, from this point, come the idea of providing the word processing system through Internet or online. WebWordPro 2.0, which is the upgraded version of Web Word Pro 1.0, is a project that will further implement the idea. Basically WebWordPro Version 2.0 is a Web-based processing system that provides users with the basic functionality of a normal word pad as in Microsoft Windows 95/98. It allows users to access it freely via Internet from a server and perform tasks like typing, saving, editing and so on. The main objective, besides enchaining the previous versions, is to build a robust, effective and easy-to-use Web-based processing system available for everyone in the Internet. WebWordPro Version 2.0 is developed using Lotus Notes and Domino R5(1), from Lotus Development Corporation(2). With the powerful database architecture system that comes with it, keeping data and accessing it anytime, anywhere will no longer be a problem. This is because it offers the availability, reliability and security of the data in the Internet. Hopefully, with the development on WebWordPro Version 2.0, it will help to ease the process of word processing and provide a better understanding to everyone about the benefits and importance of the Internet.